EDUCACIÓN FINANCIERA Y BIENESTAR LABORAL EN LA ‘UNIDAD DE MANTENIMIENTO, CAPTACIÓN E INSTALACIÓN Y REDES PRIMARIAS’ EN UNA EMPRESA ESTATAL DE LA CIUDAD DE MEDELLIN (2023)
Financial education from childhood through adolescence, if well internalised, can be applied in different facets of life, in the workplace, in the family and in the personal sphere, and is related to people's wellbeing. On this occasion, it was proposed to associate it with well-being at work. The aim of this study was to analyse the relationship between financial education and the well-being at work of personnel in the 'Maintenance, Collection and Installation and Primary Networks Unit' of a state-owned company in Medellín, as a pilot test. As a methodological strategy, the empirical-analytical paradigm was used, as it is supported by its quantitative nature, since descriptive statistics are used to process the data. Among the findings is that 60% of the respondents acknowledged having received counselling on labour welfare issues but not on Financial Education (FE). On the other hand, according to the literature review, it was found that prior knowledge in financial education brings benefits to the employee such as: greater borrowing capacity, reduced work stress, assertive financial decision-making, efficient management of resources, among others, which leads to greater well-being at work. Although no evidence of previous training in FE was found, it was possible to establish, through the responses collected, that some of the respondents have basic knowledge and find a positive relationship between the two categories in accordance with the objective studied, which constitutes the added value of this research. Although no evidence of previous training in PE was found, it was possible to establish, through the responses collected, that some of the respondents had basic knowledge and found a positive relationship between the two categories in accordance with the objective studied, which constitutes the added value of this research.